PENERAPAN HUKUM PENGADAAN BARANG/JASA PEMERINTAH SEBAGAI SENGKETA TATA USAHA NEGARA - Febby Fajrurrahman (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2019)
Goods/Services Procurement is one kind classifications of state administrative disputes whose resolutions are often incomplete, and even do not provide benefits for those who submit them. It's affected by long trial time compared to the short duration of the procurement process and the implementation of government projects, as well as a different paradigm of Administrative Judges addressing the context of Goods/ Services Procurement as a rule of public law or private law. Synchronizing the paradigms about the legal context in the procurement of goods/services among the Administrative Judges, are vital for the benefit and certainty of law in the settlement of administrative disputes over goods/services procurement.